Preparation of PSAK 109 ZIS Financial Statements Using Excel for Accounting for the Nurul Huda Jatiseeng Mosque - Yekti Nilasari; Rosidin . (UIN Siber Syekh Nurjati Cirebon, 2021)
Management of zakat requires a good accounting system and order in financial administration as well as an adequate management information system so that zakat infaq alms can be managed properly to be distributed properly to mustahiq. The fundamental problem that is often faced by managers of zakat infaq alms is standardization in the accounting system and auditing of financial statements. There are still many zakat or amil administrators who have not been able to implement their financial reporting in accordance with PSAK 109 regarding zakat accounting, infaq/alms, especially zakat amil bodies operating within the scope of villages or mosques, where they still use manual calculations. The purpose of this study is to provide an overview of the application of PSAK 109 which should be used to prepare financial reports for zakat, infaq and alms with the help of using the Microsoft Excel application. The purpose of this study is to apply the presentation of financial statements that are accountable and transparent so that they can provide performance information and financial reports to internal and external parties.This research is a qualitative descriptive study which explains the implementation of PSAK 109 application by using excel application for accounting. This study resulted in a quantitative data input model for zakat finance using the Microsoft excel application in compiling financial reports for zakat, infaq / alms in accordance with PSAK 109.Â Keywords: PSAK 109, Microsoft Excel for Accounting